Investigation of mechanical properties of polymer nanocomposites - Lim, Kai Xin. (2009)
This report documents the effect of elongation rate and moisture on the mechanical properties of nylon 6 nanoclay nanocomposites. Mechanical tests were conducted on nylon 6 nanocomposites with 0 wt%, 2 wt%, 4 wt% and 6 wt% nanoclay. Elongation rates of 5 mm/min, 40 mm/min and 120 mm/min were used to determine the effects of elongation rate. Effects of moisture were examined using specimens that were dried in a vacuum oven for 48 hours at 80ºC, at atmospheric conditions and when saturated with moisture using elongation rates of 40 mm/min and 120 mm/min. Tensile strain at yield, tensile stress and strain at maximum load and at break were found to decrease with increasing nanoclay concentration while Young’s modulus increased and yield stress showed no trend. On the other hand, Young’s modulus decreased while tensile stress and strain at maximum load and at break increased with increasing elongation rate. No trend relating the tensile stress and strain at yield with elongation rate was observed. As moisture content increased, Young’s modulus and yield stress of nylon 6 and its nanocomposites decreased while tensile stress and strain at maximum load and at break increased initially. A trade-off between ductility and modulus was observed and the reduction in stiffness at high moisture content could be compensated by increasing the nano clay content. In general, the experimental results agreed well with literature.